Reality of 3D imaging and display for industrial buildings - Koh, Kimberly Don Sin (2015)
Currently in the construction industry, many construction agencies requires BIM files to discuss the contraction project. Where in the project it involves architecture plans, infrastructures, roads, furniture, internal piping plants, and electrical circuit designs. This involves meeting with many people from different industries, architect, engineers, and designers. These people have to make different floor plans and combine them into one BIM file. The BIM file is very important because it helps to simplify many works. It saves time from drawing many AutoCAD drawings into drawing 3D blocks, hence people need not refer to different files to find information. All the information about the same project is combined into one and only one BIM file. But the currently commercially available BIM software in the market are not as user friendly as it needs to be. Free will navigation cannot be conducted within the BIM model. The information tagged to a certain object takes to many steps to reach. When viewing the 3D model, it is shown on a 2D screen. Therefore, it is not considered as a true 3D, because it does not present depth! In this final year project, BIM and virtual reality technologies are put together to solve the above mentioned problems. There were 2 different approaches applied to this project. In these 2 approaches, it made use of different types of 3D projection devices, 1 in the luminous lab, 2 that are commercially available in the market. A BIM file sample was given and tested throughout the whole project. The first approach involves building the virtual reality by capturing views from all angles in the 3D BIM model. From each same view, it further expanded to capture 2 views, a left view and a right view. These 2 views are later fused together to form a 3D image using the interlace method. Where this 3D image is later projected onto a 3D projection device- Array Display Device provided by luminous lab. This approach was later proven to not be feasible, as it involves too much time and costs. Standing from the industry point of view, as the device is not commercially available in the market and it is not portable, this approach was concluded to move on to 3D projection devices that are available in the market. The second approach build the virtual reality as a game, where the given BIM model was exported into a game software and subsequently made into a game. This approach was proved to be a faster method to create virtual reality. It also proves that making the BIM model into a game solves the problem of navigation, it is also made to become more interactive to the user. The individual 3D objects are attached with GUI layers like the texts and images. Since it was made into a game, gaming functions are also added into this environment. Examples like viewing different layers of the infrastructure of the BIM model. Performing actions like walking and jumping around the building. Adding physics element like the gravity. This approach is portrayed via 3D projection devices that are available in the market, it was tested on an active 3D television, and the oculus rift DK2. Where the 3D television shows depth when tested, and the oculus rift DK2 allows the user to experience 3D and immersion.